The influence of chemistry learning attitudes in coastal areas on understanding of knowledge related to climate change - Sabekti Ardi Widhia; Fitriani Rita; Umara Yudi (SHS Web of Conferences)
Climate change has become a global threat, especially for coastal areas. Prospective chemistry teachers in coastal areas must have a deep understanding of climate change because of their strategic role. It has never been investigated before how attitudes toward learning chemistry in coastal regions affect understanding about climate change. This study looked at how attitudes toward learning chemistry in coastal areas affected students' understanding of climate change. The participants consisted of 77 chemistry teacher candidates from a maritime university in Indonesia. Data was collected using the ALCh Instrument and the Climate Change Concept Inventory (CCCI). Simple linear regression analysis results indicated a significant effect of chemistry learning attitudes on understanding related to climate change (sig. 0.018 < 0.05). Additionally, the findings revealed that positive attitudes towards learning chemistry positively influenced the understanding of climate change, with a regression coefficient of 1.518 and R Square of 0.072.